2005
DOI: 10.1097/01.phm.0000163715.11645.96
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Precision of Ultrasonography in Patients with Carpal Tunnel Syndrome

Abstract: Ultrasonographic examination of the median nerve seems to be a promising method in the diagnosis of carpal tunnel syndrome, evaluating the morphologic changes of the median nerve in patients with clinical signs and symptoms. Further studies with wider series are needed to confirm our preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 21 publications
5
52
1
1
Order By: Relevance
“…For the determination of the optimal position on which the median nerve is most comfortable, there are catheter applications in which the intracarpal pressure is evaluated and MRI and US studies in which the AP diameter, transverse diameter and flattening ratio of the median nerve are evaluated [7][8][9][10][11][12][13][14][15][16][17]. In a study in which the CT pressure was evaluated in 20 healthy subjects, the CT pressure at 30°e xtension configuration of the wrist was found to be significantly higher when compared to 15°flexion and neutral (0°) configurations, whereas it was found to be significantly higher at 45°extension when compared to all the other angles [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the determination of the optimal position on which the median nerve is most comfortable, there are catheter applications in which the intracarpal pressure is evaluated and MRI and US studies in which the AP diameter, transverse diameter and flattening ratio of the median nerve are evaluated [7][8][9][10][11][12][13][14][15][16][17]. In a study in which the CT pressure was evaluated in 20 healthy subjects, the CT pressure at 30°e xtension configuration of the wrist was found to be significantly higher when compared to 15°flexion and neutral (0°) configurations, whereas it was found to be significantly higher at 45°extension when compared to all the other angles [7].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in which the median nerve is evaluated by MRI and US, and CT pressure is determined by using intracarpal catheter can be found in the published literature [7][8][9][10][11][12][13][14][15][16][17]. Recent research has shown that evaluation by ultrasound is promising for making CTS diagnosis [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless the demonstrated cut-off values of the CSA measurements of the median nerve range between 9-12 mm 2 with sensitivities between 73.4-99% and specificities between 57.1-100% among different studies [9,[30][31][32][33][34]. These inconsistencies could be related to the measurement of the CSA of the median nerve at different levels as well as the selection of the study sample, since age, gender, and ethnic group may affect the thickness of the median nerve.…”
Section: Rte Measurements Sr Measurements At the Level Of Carpal Tunnmentioning
confidence: 85%
“…It is well-established that anthropometric data varies among different populations. The cutoff point in the current study was 0.4 ms (distal sensory latency of the median nerve minus the distal sensory latency of by electro-diagnostic testing [14]. The prevalence rates of CTS may vary according to the diagnostic tools used.…”
Section: Ijomeh 2017;30(2) 287mentioning
confidence: 99%